Comparative evaluation of efficacy of 4% tulsi extract (Ocimum sanctum), fluoridated and placebo dentifrices against gingivitis and plaque among 14–15 years school children in Davangere City, India – A triple blinded randomized clinical trial - Bhuvaneshwari Gangadharamurthy Nadar (Contemporary Clinical Dentistry, 2020)
Context: Gingivitis is the most prevalent periodontal disease among adolescents. The most important factor associated with gingivitis is plaque accumulation. Mechanical plaque control through tooth brushing and mouth rinsing are the most commonly used preventive methods. Aims: This study aims to assess and compare the antiplaque and antigingivitis effect of 4% Tulsi leaf extract dentifrice, fluoridated and placebo dentifrice (PD) among 14–15-year-old school children in Davangere city. Materials and Methods: A triple blinded concurrent parallel trial. A sample of 84 participants with a baseline mean gingival index score of at least 1.0 and mean plaque index score of at least 1.5 were randomly selected. Participants were divided into three groups by block randomization and concealed random allocation method was used to distribute dentifrices. Postassessment of plaque and gingivitis was done on the 21st day. Statistical Analysis Used: Wilcoxon signed rank test for within group comparison and Kruskal–Wallis ANOVA for intergroup comparison was used. Results: Significant reduction in the plaque and gingival scores between the groups was observed on the 21st day (P = 0.001). Maximum reduction in gingivitis (P = 0.001) and dental plaque (P = 0.01) was seen in 4% tulsi dentifrice group compared to PD. Conclusion: Antiplaque and antigingivitis efficacy of 4% tulsi and commercially available fluoridated dentifrice remained the same after 21 days.